Periprosthetic fractures of the proximal femur within first year of the index hip prosthesis - Spina, Mauro; Scalvi, Andrea (Acta Biomedica Atenei Parmensis, 2020)
Introduction: Periprosthetic fractures are a serious complication of implants prosthetic. The aim of this review is to analyze incidence and predisposing factors of periprosthetic fractures of the proximal femur within first year of the index hip prosthesis. Materials and methods: Between 1998 and 2017 we have performed 4240 hip replacements (F 2661, M 1579): 2877 total hip arthroplasties (67,9%) and 1363 hemiartrhoplasties (32,1%). Hip replacements with cemented stem were 2173 (51,2%), while cementless ones were 2067 (48,8%). In the same period we admitted 121 hip periprosthetic fractures, 26 of which (0,6%) within the first year of the index surgery. We examined the medical and radiographic records of this last cohort of patients (F 19, M 7) following the Vancouver System, Dorr Classification and Stem Size Index. Results: The cause was a low-energy trauma in 25 cases (96.1%); the primary diagnosis was hip fracture in 20 patients (76.9%); 8 patients were taking chronic osteoporosis medication (30.7%); 14 patients were affected by neuropsychiatric disease (53.8%); cementless stems were found in 18 cases, 12 of which were oversized (SSI < 0,8). According to Vancouver System, fractures were classified as follows: 10 type B1, 14 type B2 and 2 type C. As far as the proximal femoral shape, 2 cases were Dorr type A, 7 Dorr type B and 17 Dorr type C. Conclusions: The incidence of periprosthetic fractures in the aftermath of stem implant is twice as high with uncemented stems. The Vancouver type B1/B2 is the most common. Predisposing factors are: female sex, hip fracture, chronic osteoporosis medication, neuropsychiatric disease and oversized uncemented stem (SSI < 0.8).The evidence level is IV.